2010
DOI: 10.1007/s10144-010-0195-8
|View full text |Cite
|
Sign up to set email alerts
|

Do seed harvesting ants threaten the viability of a critically endangered non‐myrmecochorous perennial plant population? A complex interaction

Abstract: This study analyzes the fate of seeds removed by ants, as well as the seed supply, seedling survival, and the ability to form persistent seed banks in the soil, in a critically endangered population of the non-myrmecochorous perennial halophyte Helianthemum polygonoides, in order to determine the extent to which seed removal by ants represents a real bottleneck for recruitment and thus a threat for long-term population viability. Apparently, the impact of seed-harvester ants was dramatic: the primary seed shad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Furthermore, matrix models of population viability have demonstrated that the demographic bottleneck of H. polygonoides is in the abundance of mature individuals (i.e., age range which will be only negatively affected if the habitat is destroyed) (Copete et al 2009;Martínez-Duro et al 2010). Those ecological features support our ndings and contribute to understand the chorological and demographic trends of H. polygonoides.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, matrix models of population viability have demonstrated that the demographic bottleneck of H. polygonoides is in the abundance of mature individuals (i.e., age range which will be only negatively affected if the habitat is destroyed) (Copete et al 2009;Martínez-Duro et al 2010). Those ecological features support our ndings and contribute to understand the chorological and demographic trends of H. polygonoides.…”
Section: Discussionsupporting
confidence: 74%
“…A persistent seed bank can be crucial in ensuring the conservation of a species, since it allows the re-establishment and maintenance of plant populations after disturbances, although no external source of propagules occurs (Baskin & Baskin 1978). In fact, Thompson et al (1997) suggested that short-term persistent soil seed banks play an essential role in the viability of populations, as Martínez-Duro et al (2010) empirically demonstrated for a critically endangered perennial plant species.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of viable recovered seeds were reduced, with 262 and 294 seeds/m 2 for A. belladonna and A. baetica, respectively, but these values are very important in a population dynamics context because these species are unusual and the formation of persistent soil seeds banks can allow the recruitment of seedlings for years, especially when fruit formation might be affected by events such as herbivory or destruction by summer storms [18]. Similarly, population viability analyses have also stressed the important roles of soil seed banks in the long-term persistence of populations of perennials, such as Helianthemum polygonoides, which is a critically endangered perennial shrub in southeast Spain [38]. Vegetative propagation appears to be more important for seedling recruitment than seed germination for the study species, but seeds play a crucial role in the renewal of adult individuals, which can live more than 20 years (personal observation), although they inevitably die.…”
Section: Discussionmentioning
confidence: 99%